Understanding Advanced Prostate Cancer Decision Making Utilizing an Interactive Decision Aid. Issue 1 (January 2018) - Jones, Randy A.; Hollen, Patricia J.; Wenzel, Jennifer; Weiss, Geoff; Song, Daniel; Sims, Terran; Petroni, Gina
Abstract : Background: Prostate cancer is the most commonly diagnosed cancer and the second leading cause of cancer deaths among men in the United States. Patients with advanced prostate cancer are vulnerable to difficult treatment decisions because of the nature of their disease. Objective: The aims of this study were to describe and understand the lived experience of patients with advanced prostate cancer and their decision partners who utilized an interactive decision aid, DecisionKEYS, to make informed, shared treatment decisions. Methods: This qualitative study uses a phenomenological approach that included a sample of 35 pairs of patients and their decision partners (16 pairs reflected patients with <6 months since their diagnosis of metastatic castration-resistant prostate cancer; 19 pairs reflected patients with >6 months since their diagnosis of metastatic castration-resistant prostate cancer). Qualitative analysis of semistructured interviews was conducted describing the lived experience of patients with advanced prostate cancer and their decision partners using an interactive decision aid. Results: Three major themes emerged: (1) the decision aid facilitated understanding of treatment options; (2) quality of life was more important than quantity of life; and (3) contact with healthcare providers greatly influenced decisions. Conclusions: Participants believed the decision aid helped them become more aware of their personal values, assisted in their treatment decision making, and facilitated an interactive patient–healthcare provider relationship. Implications for Practice: Decision aids assist patients, decision partners, and healthcare providers make satisfying treatment decisions that affect quality/quantity of life. These findings are important for understanding the experiences of patients who have to make difficult decisions.